(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To compare the effects of warm acupuncture combined with Gabapentin versus Gabapentin alone on quality of life in people with postherpetic neuralgia, based on changes in the SF-36 score after 4 weeks of treatment. Method: A randomized controlled clinical trial was conducted at Le Van Thinh Hospital from July 2024 to April 2025. A total of 36 people with postherpetic neuralgia of Qi stagnation and Blood stasis pattern were randomly assigned to two groups: the intervention group (warm acupuncture + Gabapentin) and the control group (Gabapentin alone). The treatment lasted 4 weeks. Effectiveness was assessed by changes in SF-36 scores. Results: After 4 weeks, both groups showed significant improvement in SF-36 scores compared to baseline (p < 0.001). The intervention group demonstrated greater improvement than the control group (increase of 34.85 vs. 23.82 points; p < 0.001), with significantly higher mean SF-36 scores after treatment (71.37 vs. 58.34 points; p = 0.011). Conclusion: Warm acupuncture combined with Gabapentin improved quality of life more effectively than Gabapentin alone in people with postherpetic neuralgia after 4 weeks.